Decentralisation and local governments : the Indian experience - Raghunandan, T. R.; Tata Institute of Social Sciences (New Delhi : Orient Blackswan, 2012)
Contributed articles.
"Tata Institute of Social Sciences."
"Essays from Economic and political weekly"--Cover.
Includes bibliographical references.
BIGD
Keywords: Decentralization in government -- India; Local government -- India